2006
DOI: 10.1105/tpc.105.040568
|View full text |Cite
|
Sign up to set email alerts
|

TheTORNADO1andTORNADO2Genes Function in Several Patterning Processes during Early Leaf Development inArabidopsis thaliana

Abstract: In multicellular organisms, patterning is a process that generates axes in the primary body plan, creates domains upon organ formation, and finally leads to differentiation into tissues and cell types. We identified the Arabidopsis thaliana TORNADO1 (TRN1) and TRN2 genes and their role in leaf patterning processes such as lamina venation, symmetry, and lateral growth. In trn mutants, the leaf venation network had a severely reduced complexity: incomplete loops, no tertiary or quaternary veins, and vascular isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
145
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(151 citation statements)
references
References 49 publications
4
145
1
1
Order By: Relevance
“…Available evidence, however, suggests that the selection process terminates with emergence of files of ground cells that have activated expression of the HD-ZIP III gene ATHB8 and that will successively elongate into procambial cells (AlonsoPeral et al, 2006;Candela et al, 2001;Carland and Nelson, 2004;Cnops et al, 2006;Donner et al, 2009;Kang and Dengler, 2004;Koizumi et al, 2000;Petricka and Nelson, 2007;Sawchuk et al, 2007Sawchuk et al, , 2008Scarpella et al, 2004Scarpella et al, , 2006. Therefore, the events preceding acquisition of the ATHB8 preprocambial cell state are crucial for vein formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available evidence, however, suggests that the selection process terminates with emergence of files of ground cells that have activated expression of the HD-ZIP III gene ATHB8 and that will successively elongate into procambial cells (AlonsoPeral et al, 2006;Candela et al, 2001;Carland and Nelson, 2004;Cnops et al, 2006;Donner et al, 2009;Kang and Dengler, 2004;Koizumi et al, 2000;Petricka and Nelson, 2007;Sawchuk et al, 2007Sawchuk et al, , 2008Scarpella et al, 2004Scarpella et al, , 2006. Therefore, the events preceding acquisition of the ATHB8 preprocambial cell state are crucial for vein formation.…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of ATHB8 expression is directly controlled by MP (Donner et al, 2009), and identifies acquisition of a critical and typically irreversible 'preprocambial' cell state that accurately predicts sites of vascular differentiation (Alonso-Peral et al, 2006;Candela et al, 2001;Carland and Nelson, 2004;Cnops et al, 2006;Donner et al, 2009;Kang and Dengler, 2004;Koizumi et al, 2000;Petricka and Nelson, 2007;Pineau et al, 2005;Sawchuk et al, 2007Sawchuk et al, , 2008Scarpella et al, 2004Scarpella et al, , 2006. A view of the transcriptional landscape of cells at preprocambial stages would be particularly valuable as it might provide insight into the molecular pathways underlying vein formation.…”
Section: Introductionmentioning
confidence: 99%
“…However, this extracellular loop is not a defining feature of TET function, since it is absent in a subgroup of human TETs called the fourtransmembrane L6 superfamily (Wright et al, 2000). Of the 17 TET genes in Arabidopsis (Wang et al, 2012), one, TET1/TORNADO2/EKEKO, has been shown to be required for leaf and root patterning (Olmos et al, 2003;Cnops et al, 2006). In addition, like vcc and ops mutant lines, mutants in TET1/TORNADO2/EKEKO also show defects in cotyledon vein patterning (Cnops et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 17 TET genes in Arabidopsis (Wang et al, 2012), one, TET1/TORNADO2/EKEKO, has been shown to be required for leaf and root patterning (Olmos et al, 2003;Cnops et al, 2006). In addition, like vcc and ops mutant lines, mutants in TET1/TORNADO2/EKEKO also show defects in cotyledon vein patterning (Cnops et al, 2006). Some plant TETs localize to the plasma Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…Onset of ATHB8 expression is directly controlled by MP (Donner et al, 2009), and identifies transition to a typically irreversible ''preprocambial'' cell state that accurately predicts sites of leaf vein formation (e.g., Koizumi et al, 2000;Carland and Nelson, 2004;Kang and Dengler, 2004;Scarpella et al, 2004Scarpella et al, , 2006Pineau et al, 2005;Alonso-Peral et al, 2006;Cnops et al, 2006;Petricka and Nelson, 2007;Sawchuk et al, 2007Sawchuk et al, , 2008Donner et al, 2009;Carland et al, 2010). Therefore, characterization of the transcriptional profile of ground cells that have switched to preprocambial state would be particularly desirable as it may provide insight into the molecular pathways controlling vein formation.…”
Section: Introductionmentioning
confidence: 99%